94.5k views
4 votes
What is the solution: 12 = 6 –5x + 3x

User Molokoka
by
4.8k points

1 Answer

0 votes

Answer:

x = -3

Explanation:

Step 1: Write equation

12 = 6 - 5x + 3x

Step 2: Solve for x

  1. Combine like terms: 12 = 6 - 2x
  2. Subtract 6 on both sides: 6 = -2x
  3. Divide -2 on both sides: -3 = x
  4. Rewrite: x = -3

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute: 12 = 6 - 5(-3) + 3(-3)
  2. Multiply: 12 = 6 + 15 - 9
  3. Add: 12 = 21 - 9
  4. Subtract: 12 = 12
User Jonathan Kittell
by
5.0k points